Cation supplementing material and preparation method thereof, electrolyte, positive pole piece, negative pole piece, diaphragm, battery and electric device

By using shell-coated non-M element cationic salts as cationic supplementary materials in lithium-ion batteries, the problem of cation consumption of the battery during circulation is solved, the cycling performance of the battery is improved and the cost is reduced.

CN119852559APending Publication Date: 2025-04-18CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311352006.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-18
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

During the circulation process, the existing lithium-ion batteries have caused the added potassium or sodium salts to be gradually consumed in the early cycle, losing the function of improving long-term circulation.

Method used

A cationic supplementary material is used, which includes a shell and a core material, which contains a non-M element cationic salt. By covering the core material in the shell, the release of non-M element cationic salts in the melting or early cycle is reduced, so that they are released into the electrolyte in the middle and late stages of the cycle, replenishing the cations consumed in the battery.

Benefits of technology

It effectively improves the cycling performance of the battery, extends the cycling life of the battery, and reduces the cost of the battery, especially when using non-lithium salts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852559A_ABST
    Figure CN119852559A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a cation supplementing material and a preparation method thereof, an electrolyte, a positive pole piece, a negative pole piece, a diaphragm, a battery and an electric device. The cation supplementing material comprises a core material and a shell layer arranged on the surface of the core material, and the core material comprises non-M element cation salt. The surface of the non-M element cation salt is coated with the shell layer, so that release of the non-M element cation salt into the electrolyte in the initial stage of formation or circulation is reduced, the non-M element cation salt is released into the electrolyte in the middle and later stages of circulation, cations consumed in the battery are supplemented, and the cycle performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a cation-supplementing material and a preparation method thereof, an electrolyte, a positive electrode sheet, a negative electrode sheet, a separator, a battery and an electrical device. Background Art

[0002] With the rapid growth of portable electronic devices and electric vehicles, the demand for power batteries is also growing. Among them, the electrochemical performance of batteries is also attracting more and more attention.

[0003] Due to some irreversible reactions such as the formation of the solid electrolyte membrane (SEI membrane) on the surface of the negative electrode during the initial charge and discharge formation process, the positive electrode material will experience ion loss, which will lead to a decrease in the cycle performance of the battery. Taking lithium-ion batteries as an example, in the prior art, in order to solve the above problem, a lithium supplement is added to the battery to supplement the lithium ions lost during the initial formation process. Summary of the invention

[0004] The main purpose of the present invention is to provide a cation-supplementing material, aiming to improve the cycle performance of the battery.

[0005] To achieve the above object, the present invention proposes a cation-supplementing material for use in M-element batteries, comprising a shell layer and a core material disposed in the shell layer, wherein the core material comprises a non-M-element cation salt.

[0006] During the cycle, due to SEI film consumption, electrolyte decomposition and other reasons, the added potassium salt or sodium salt will be gradually consumed in the early cycle and deposited on the negative electrode in the form of salt or dead metal elements, losing its improvement function for long-term cycles, especially in the later stages of the cycle.

[0007] In order to solve the above problems, the core material is coated in the shell layer, and the core material includes a non-M element cation salt, which helps to reduce the release of the non-M element cation salt into the electrolyte during formation or the initial stage of circulation, so that the non-M element cation salt is released into the electrolyte in the middle and late stages of the cycle, replenishing the cations consumed in the battery and improving the cycle performance of the battery.

[0008] It can be understood that, when the M element includes lithium, the non-M element cation salt is a non-lithium salt, for example, the non-lithium salt includes potassium perchlorate, sodium tetrafluoroborate, and the like.

[0009] It is understandable that these non-M element cation salts can participate in the formation of the SEI film. For example, taking a lithium-ion battery as an example, that is, the M element battery is a lithium-ion battery, and the non-M element cation salt is a non-lithium salt, such as sodium salt, magnesium salt, etc. These non-M element cation salts (such as sodium salt, magnesium salt) can be deposited on the surface of the negative electrode to repair the SEI film; in addition, the non-M element cation salt can also play the role of electrostatic shielding and inhibit the growth of lithium dendrites. Since the above-mentioned non-lithium salts can be dissolved into the electrolyte in the middle and late stages of the cycle, they have a significant effect on the improvement of the battery cycle in the middle and late stages.

[0010] It is understandable that if Figure 1 , which is a schematic structural diagram of a cation-supplementing material, the surface of a core material 10 is coated with a shell layer 20 .

[0011] Optionally, the non-M element cation in the non-M element cation salt includes at least one of a Group IA element cation or a Group IIA element cation.

[0012] It is understandable that information on Group IA elements and Group IIA elements can be obtained from the periodic table. For example, Group IA elements include sodium, potassium, etc., and Group IIA elements include calcium, magnesium, etc.

[0013] Optionally, the M element battery comprises a lithium battery, and the non-M element cation in the non-M element cation salt comprises one or more of potassium ion, sodium ion, barium ion, cesium ion, rubidium ion and calcium ion;

[0014] Alternatively, the M element battery comprises a sodium battery, and the non-M element cations in the non-M element cation salt comprise one or more of potassium ions, lithium ions, barium ions, cesium ions, rubidium ions and calcium ions.

[0015] It can be understood that the M element battery of the present application includes but is not limited to a lithium battery or a sodium battery.

[0016] The M element battery includes a lithium battery, and the non-M element cations in the non-M element cation salt include but are not limited to one or more of potassium ions, sodium ions, barium ions, cesium ions, rubidium ions and calcium ions.

[0017] The M element battery includes a sodium battery, and the non-M element cations in the non-M element cation salt include but are not limited to one or more of potassium ions, lithium ions, barium ions, cesium ions, rubidium ions and calcium ions.

[0018] It is understandable that when the M element battery is a lithium battery, the non-M element cation salt includes a non-lithium salt. Considering that for lithium-ion batteries, the price of lithium salts is often relatively expensive, which increases the cost of the battery. For this reason, non-lithium salts are used to supplement cations, thereby improving the battery cycle performance and reducing costs.

[0019] Optionally, the anions in the non-M element cation salt include at least one of perchlorate, tetrafluoroborate, hexafluoroarsenate, hexafluorophosphate, bistrifluoromethylsulfonyl imide, difluorophosphate, bisdifluorosulfonyl imide, bisoxalatoborate and difluorooxalatoborate, nitrate, sulfate, sulfite, and trifluoromethanesulfonyl.

[0020] It is understood that the anions in the non-M element cation salt include but are not limited to at least one of perchlorate, tetrafluoroborate, hexafluoroarsenate, hexafluorophosphate, bistrifluoromethylsulfonyl imide, difluorophosphate, bisdifluorosulfonyl imide, bisoxalate borate and difluorooxalate borate, nitrate, sulfate, sulfite, and trifluoromethanesulfonyl.

[0021] Considering that the anions in the non-M element cation salts in the common electrolytes of the above anions include the above anions, the applicability of the non-M element cation salts in batteries can be improved. In addition, the salts composed of the above anions and the non-M element cations can be effectively dissolved in the electrolyte.

[0022] Optionally, the mass percentage of the non-M element cation salt to the mass of the cation-supplementing material is 50% to 99%, preferably 70% to 95%.

[0023] In order to effectively encapsulate the core material in the shell layer and to have a shell layer of suitable thickness, the mass percentage of the non-M element cation salt to the mass percentage of the cation-supplementing material is 50% to 99%, preferably 70% to 95%.

[0024] Optionally, the Dv50 value of the cation-supplementing material is in the range of 100 nm to 10 μm, preferably, 200 nm to 2 μm.

[0025] If the Dv50 of the cation-supplementing material is too small, the coating property of the shell is poor and it is difficult to form a coating state; if the Dv50 of the cation-supplementing material is too large, when the cation-supplementing material is set on the positive electrode plate or the negative electrode plate, after the cation-supplementing material is decomposed, larger pores will be left in the positive electrode coating or the negative electrode coating, the mechanical properties of the plate will be reduced, and the coating will easily collapse and break. When the cation-supplementing material is prepared into a slurry and applied to the diaphragm, if the Dv50 of the cation-supplementing material is too large, it is difficult to obtain a cation-supplementing material coating of suitable thickness. When the cation-supplementing material is added to the electrolyte, if the Dv50 of the cation-supplementing material is too small, the pores of the plate or the diaphragm may be blocked during formation or the initial stage of circulation. If the Dv50 of the cation-supplementing material is too large, it may hinder the electrolyte from wetting the plate or the diaphragm.

[0026] Therefore, taking all factors into consideration, the Dv50 range of the cation-supplementing material is 100 nm to 10 μm, preferably 200 nm to 2 μm.

[0027] Optionally, the thickness of the shell layer ranges from 20 nm to 800 nm, preferably from 50 nm to 200 nm;

[0028] And / or, the shell layer completely covers the surface of the core material.

[0029] Considering that the wall thickness of the shell layer has an impact on the cation-supplementing material and the cation replenishment in the middle and late stages of the cycle, for example, when the shell layer is at a certain thickness, the longer the period of release of the non-M element cation salt in the cation-supplementing material into the electrolyte, the more continuously the cations can be replenished, and the cycle performance will be improved. However, when the thickness of the shell layer is too thick, the shell layer is difficult to be swollen by the solvent in the electrolyte or etched by the acid, which is not conducive to the release of the non-M element cation salt. For example, in the worst case, when the cycle life of the battery reaches the end, the non-M element cation salt is released into the electrolyte to replenish the cations, and it is difficult to improve the performance of the battery at this time. For this reason, based on comprehensive considerations, the thickness range of the shell layer is 20nm to 800nm, preferably 50nm to 200nm.

[0030] It can also be understood that, in theory, the non-M element cation salt in the shell layer in the present application can be solid or liquid. Preferably, the non-M element cation salt in the shell layer in the present application can be solid (it can be understood that a drying step will be performed during the preparation of the cation-supplementing material, and the non-M element cation salt solution coated in the shell layer will be dried during the drying process.). On the one hand, the solid non-M element cation salt in the shell layer occupies less space than the liquid non-M element cation salt solution, which is conducive to the preparation of small-sized cation-supplementing materials. At the same time, the mass of the solvent in the non-M element cation salt solution can also be subtracted, thereby reducing the overall mass of the cation-supplementing material. When the cation-supplementing material is added to the battery, it helps to improve the energy density of the battery.

[0031] In addition, the solid state has mechanical strength compared to the liquid state. During the extrusion process of the positive electrode sheet, the negative electrode sheet and the diaphragm, the cation-supplementing material is not easily crushed or broken. It is difficult for the shell of the cation-supplementing material to be damaged due to the extrusion process during the preparation process, thereby reducing the direct release of non-M element cation salts in the shell and improving the subsequent cation replenishment in the battery cycle.

[0032] In one embodiment, the shell layer completely covers the surface of the core material.

[0033] Full coverage means that the shell layer is continuously covered on the surface of the core material, and the surface of the core material is not exposed.

[0034] In order to reduce the exposure of the core material to the electrolyte during the formation process or the early stage of the cycle, it is preferred that the shell layer completely covers the surface of the core material. In this way, the shell layer is etched by the acidic substances (such as HF) generated during the battery cycle, or the shell layer is swollen by immersion in the electrolyte to form pores, thereby slowly exposing the core material, which is helpful for the replenishment of cations in the middle and late stages of the cycle.

[0035] Optionally, the material of the shell layer includes at least one of a gelatin-modified amino resin composite material, a styrene-butadiene rubber polymer, and an acrylate polymer.

[0036] It is understandable that the material of the shell layer includes but is not limited to at least one of a gelatin-modified amino resin composite material, a styrene-butadiene rubber polymer, and an acrylate polymer.

[0037] Gelatin is a peptide molecule polymer and a multi-level hydrolysis product of collagen. Its molecular formula is AlH 3 KO 8 S 2 .

[0038] Amino resin is a general term for resins formed by condensation of amino-containing compounds and formaldehyde.

[0039] Styrene butadiene rubber, also known as polystyrene butadiene copolymer, can be copolymerized by monomers such as styrene and butadiene.

[0040] Acrylate polymer, during the polymerization process, the monomers include acrylate monomers, for example, acrylonitrile, methyl methacrylate, azobisisobutyronitrile, triallyl isocyanurate are mixed and heated to react to obtain the acrylate polymer.

[0041] For example, gelatin-modified amino resin is used as the shell layer, wherein gelatin has good coating and etching properties, and the addition of amino resin can enhance the mechanical properties of gelatin, so the two form a composite shell layer, improving the functionality and mechanical properties of the shell layer.

[0042] The shell layer is used to slow down the release rate of the non-M element cation salt inside the shell layer. Specifically, during the early cycle of the battery, due to the coating effect of the shell layer, the internal non-M element cation salt is difficult to be dissolved into the electrolyte for cation replenishment. During the long-term cycle process, the electrolyte will produce trace acidic substances, which will gradually etch the surface of the shell layer (for example, gelatin-modified amino resin), and then the non-M element cation salt inside the shell layer will gradually be exposed and dissolved in the electrolyte, which can play a good role in long-term cyclic cation replenishment.

[0043] It can also be understood that, in addition to being etched by the acidic substances in the electrolyte, the shell layer can also utilize the shell layer material (such as polyurea resin) to swell under long-term immersion in the electrolyte to form a porous structure. The non-M element cation salt in the shell layer is gradually exposed from the porous position, contacts with the electrolyte, and dissolves in the electrolyte, which can play a good role in long-term cyclic cation replenishment.

[0044] Optionally, the shell layer comprises at least two shell layers, at least one shell layer is arranged on the surface of the core material, and at least another shell layer is arranged on a side of the at least one shell layer away from the core material;

[0045] And / or, the shell layer comprises at least two shell layers, at least one shell layer is arranged on the surface of the core material, and at least another shell layer is arranged on a side of the at least one shell layer away from the core material, and the thickness of the at least one shell layer ranges from 10nm to 400nm, preferably, from 30nm to 150nm;

[0046] And / or, the shell layer includes at least two shell layers, at least one shell layer is arranged on the surface of the core material, and at least another shell layer is arranged on the side of the at least one shell layer away from the core material, and the thickness range of the at least another shell layer is 10nm to 400nm, preferably, 30nm to 150nm.

[0047] In order to improve the coating effect of the shell layer on the core material, at least two layers of shell are used, for example, two layers, three layers, etc. Figure 2 As shown, the shell layer 20 includes a layer shell 21 and another side shell 22 .

[0048] It is understandable that, since non-M element cation salts are easily soluble in electrolyte, the shell layer needs to have good coating properties to isolate the electrolyte; at the same time, in order to play a role of sustained release in the middle and late stages of the cycle, the shell also needs to have the characteristics of being etched by acid (such as HF) or being swollen by the electrolyte to produce pores. In addition, in order to ensure the completeness of the shell, it also needs to have good mechanical properties.

[0049] Based on the above requirements, a single-component shell is difficult to meet the requirements of coating, etching, mechanical strength, porosity, etc. For example, a single-component gelatin shell has coating and etching properties, but poor mechanical properties, and a single-component styrene-butadiene rubber has good mechanical properties, but its coating properties are poor.

[0050] For example, in the structure of the two-layer shell, the present application uses gelatin-modified amino resin composite material as the first layer shell to provide good coating and etchability; styrene-butadiene rubber polymer is used as the second layer shell to improve the compactness, toughness and heat resistance of the shell, thereby improving its thermal processing stability. The combination of the two plays a role in taking advantage of each other's strengths and making up for each other's weaknesses.

[0051] Furthermore, in order to ensure that each shell has good coating properties and can also be etched or swelled under the action of the electrolyte in the middle and late stages of the battery cycle to release the non-M element cation salt into the electrolyte, the thickness of at least one shell layer ranges from 10 nm to 400 nm, preferably, from 30 nm to 150 nm; the thickness of at least another shell layer ranges from 10 nm to 400 nm, preferably, from 30 nm to 150 nm.

[0052] Optionally, the material of the at least one shell layer comprises a gelatin-modified amino resin composite material;

[0053] And / or, the material of the at least another shell layer includes at least one of styrene-butadiene rubber polymer and acrylate polymer.

[0054] It is understandable that the material of at least one shell layer includes but is not limited to gelatin-modified amino resin composite material; the material of at least another shell layer includes but is not limited to at least one of styrene-butadiene rubber polymer and acrylate polymer.

[0055] Optionally, the present application also provides an electrolyte, which includes the cation-supplementing material as described.

[0056] By directly adding the cation-replenishing material into the electrolyte, the non-M element cation salt in the shell can be slowly exposed during the battery cycle, so that the non-M element cation salt dissolves in the electrolyte, which can play a good role in long-term cyclic cation replenishment.

[0057] For example, it is understandable that in the early cycle, due to the coating effect of the shell layer, the non-M element cation salt inside cannot overflow and dissolve. In the long-term cycle process, the electrolyte will produce trace acidic substances, which will gradually etch the surface of the microshell layer, and then the non-M element cation salt inside the shell layer will gradually be exposed and dissolved in the electrolyte.

[0058] Optionally, the mass percentage of the cation-supplementing material to the total mass of the electrolyte is 1% to 100%, preferably 5% to 20%.

[0059] Considering that if the mass of the cation-replenishing material inside the battery is insufficient, it will be difficult to sufficiently replenish cations in the middle and late stages of the battery cycle. At the same time, if the mass of the cation-replenishing material inside the battery is too much, there will be excessive cation replenishment, making it difficult to further improve the cycle performance, and at the same time, the mass energy density of the battery will be reduced. For this reason, when the cation-replenishing material is directly added to the electrolyte, the mass percentage of the mass of the cation-replenishing material to the total mass of the electrolyte is in the range of 1% to 100%, preferably 5% to 20%.

[0060] Optionally, the mass percentage of the non-M element cation salt in the cation-supplementing material to the total mass of the electrolyte is 0.0001% to 50%, preferably 0.5% to 10%.

[0061] It is understood that when the cation-supplementing material is added to the electrolyte, the mass percentage of the non-M element cation salt in the added cation-supplementing material to the total mass of the electrolyte is 0.0001% to 50%, preferably 0.5% to 10%. This helps to improve the cycle performance of the battery.

[0062] Optionally, the electrolyte includes a lithium salt, and the lithium salt includes at least one of lithium perchlorate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium difluorophosphate, lithium bis(difluorosulfonyl)imide, lithium bis(oxalatoborate), lithium difluorooxalatoborate, and lithium trifluoromethanesulfonyl;

[0063] And / or, the electrolyte includes a solvent, and the solvent includes at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and fluoroethylene carbonate.

[0064] When the battery is a lithium battery, the electrolyte includes a lithium salt, and the lithium salt includes but is not limited to at least one of lithium perchlorate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium difluorophosphate, lithium bis(difluorosulfonyl)imide, lithium bis(oxalatoborate), lithium difluorooxalatoborate, and lithium trifluoromethanesulfonyl.

[0065] The electrolyte includes a solvent, and the solvent includes but is not limited to at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and fluoroethylene carbonate.

[0066] Optionally, the present application also provides a positive electrode plate, wherein the positive electrode plate comprises the cation-supplementing material as described.

[0067] It is understandable that the cation-supplementing material can be added inside the positive electrode coating or disposed on the surface of the positive electrode coating.

[0068] Optionally, the positive electrode plate includes a positive electrode current collector and a positive electrode coating provided on the positive electrode current collector, and the mass percentage of the cation-supplementing material to the total mass of the positive electrode coating is 0.5% to 20%, preferably 1% to 5%.

[0069] On the one hand, if the mass of the cation-replenishing material inside the battery is insufficient, it will be difficult to sufficiently replenish cations in the middle and late stages of the battery cycle. At the same time, if the mass of the cation-replenishing material inside the battery is too much, there will be excessive cation replenishment, making it difficult to further improve the cycle performance, and at the same time reducing the mass energy density of the battery.

[0070] On the other hand, considering that non-M element cation salts will dissolve into the electrolyte during the circulation process, thereby leaving pores in the positive electrode coating, if too much cation-supplementing material is added to the positive electrode coating, the porosity of the positive electrode coating will increase in the later stage of the cycle. If the porosity is too high, although the wettability of the positive electrode coating to the electrolyte can be improved, the mechanical strength of the positive electrode coating will decrease, and the positive electrode coating will be prone to collapse and rupture. Therefore, taking all factors into consideration, the mass percentage of the cation-supplementing material to the total mass of the positive electrode coating is in the range of 0.5% to 20%, preferably 1% to 5%.

[0071] Optionally, the positive electrode coating includes a binder, and the mass percentage of the binder in the positive electrode coating to the total mass of the positive electrode coating is 0.5% to 10%, preferably 1% to 3%.

[0072] Taking into account the adhesive properties of the shell layer of the cation-supplementing material, when the cation-supplementing material is added into the positive electrode coating, the amount of the binder added into the positive electrode coating can be reduced accordingly. To this end, the mass percentage of the binder in the positive electrode coating to the total mass of the positive electrode coating is 0.5% to 10%, preferably 1% to 3%.

[0073] Optionally, the positive electrode plate includes a positive electrode current collector and at least two layers of positive electrode coatings provided on the positive electrode current collector, at least one of the positive electrode coatings is provided on the positive electrode current collector, and at least another positive electrode coating is provided on the side of at least one of the positive electrode coatings away from the positive electrode current collector, and the mass percentage of the mass of the cation-replenishing material in at least one of the positive electrode coatings to the mass of at least one of the positive electrode coatings is defined as W1, and the mass percentage of the mass of the cation-replenishing material in at least another of the positive electrode coatings to the mass of at least another of the positive electrode coatings is defined as W2, satisfying that W2 is greater than W1.

[0074] It is understandable that in order to facilitate the shell damage and effectively dissolve the non-M element cation salt inside the shell into the electrolyte, the shell needs to contact the electrolyte. When the cation supplement material is added to the positive electrode coating, the probability of contacting the electrolyte is different at different positions of the positive electrode coating.

[0075] In order to facilitate the contact of cation-supplementing materials with the electrolyte, Figure 3As shown, the positive electrode plate 100 includes at least two layers of positive electrode coatings, at least one positive electrode coating 102 is arranged on the positive electrode current collector 101, and at least another positive electrode coating 103 is arranged on the side of the at least one positive electrode coating 102 away from the positive electrode current collector 101, so that the at least another positive electrode coating 103 is closer to the surface of the entire positive electrode coating, increasing the probability of contact with the electrolyte; and it is defined that the mass percentage of the cation-replenishing material in the at least one positive electrode coating 102 to the mass percentage of the at least one positive electrode coating 102 is W1, and the mass percentage of the cation-replenishing material in the at least another positive electrode coating 103 to the mass percentage of the at least another positive electrode coating 103 is W2, satisfying that W2 is greater than W1, that is, the mass percentage of the cation-replenishing material in the at least two layers of positive electrode coatings is distributed in a concentration gradient; at this time, the mass percentage of the cation-replenishing material in the at least another positive electrode coating 103 is greater than the mass percentage of the cation-replenishing material in the at least one positive electrode coating 102, which helps the cation-replenishing material in the at least another positive electrode coating 103 to contact the electrolyte.

[0076] At the same time, after the cation-replenishing material is decomposed, it helps to improve the porosity of the at least another positive electrode coating 103. The improvement of the porosity of the at least another positive electrode coating 103 can further improve the wetting of the positive electrode coating with the electrolyte, so that the electrolyte infiltrates into at least one positive electrode coating 102, improves the contact of the cation-replenishing material in at least one positive electrode coating 102 with the electrolyte, and improves the contact between the cation-replenishing material in at least one positive electrode coating 102 and the electrolyte. In addition, the cation-replenishing material in at least two layers of positive electrode coatings is distributed in a gradient, which can extend the period of slow release of the cation-replenishing material and improve the battery cycle performance.

[0077] Optionally, the present application also provides a negative electrode plate, wherein the negative electrode plate includes the cation-supplementing material as described.

[0078] It is understandable that, taking lithium-ion batteries as an example, considering that lithium dendrites are mainly generated at the negative electrode, cation-supplementing materials are added to the negative electrode coating so that after the cations are released, they are first at the negative electrode, and the electrostatic shielding effect of the cations is utilized to inhibit the growth of lithium dendrites.

[0079] Optionally, the negative electrode plate includes a negative electrode current collector and a negative electrode coating provided on the negative electrode current collector, and the mass percentage of the cation-supplementing material to the total mass of the negative electrode coating is 0.5% to 40%, preferably 1% to 5%.

[0080] On the one hand, if the mass of the cation-replenishing material inside the battery is insufficient, it will be difficult to sufficiently replenish cations in the middle and late stages of the battery cycle. At the same time, if the mass of the cation-replenishing material inside the battery is too much, there will be excessive cation replenishment, making it difficult to further improve the cycle performance, and at the same time reducing the mass energy density of the battery.

[0081] On the other hand, considering that non-M element cation salts will dissolve into the electrolyte during the circulation process, thereby leaving pores in the negative electrode coating, if too much cation-supplementing material is added to the negative electrode coating, the porosity of the negative electrode coating will increase in the later stage of the cycle. If the porosity is too high, the mechanical strength of the negative electrode coating will decrease, and the negative electrode coating will be prone to collapse and rupture. Therefore, based on comprehensive considerations, the mass percentage of the cation-supplementing material to the total mass of the negative electrode coating is in the range of 0.5% to 40%, preferably 1% to 5%.

[0082] Optionally, the negative electrode coating includes a binder, and the mass percentage of the binder in the negative electrode coating to the total mass of the negative electrode coating is 0.5% to 15%, preferably 1% to 5%.

[0083] Taking into account the adhesive properties of the shell layer of the cation-supplementing material, when the cation-supplementing material is added into the negative electrode coating, the amount of the binder added into the negative electrode coating can be reduced accordingly, and the mass percentage of the binder in the negative electrode coating to the total mass of the negative electrode coating is 0.5% to 15%, preferably 1% to 5%.

[0084] Optionally, the negative electrode plate includes a negative electrode current collector and at least two layers of negative electrode coatings provided on the negative electrode current collector, at least one of the negative electrode coatings is provided on the negative electrode current collector, and at least another negative electrode coating is provided on the side of at least one of the negative electrode coatings away from the negative electrode current collector, and the mass percentage of the cation-replenishing material in at least one of the negative electrode coatings to the mass percentage of the at least one of the negative electrode coatings is defined as W3, and the mass percentage of the cation-replenishing material in at least another of the negative electrode coatings to the mass percentage of the at least another of the negative electrode coatings is defined as W4, satisfying that W4 is greater than W3.

[0085] It is understandable that in order to facilitate the shell damage and effectively dissolve the non-M element cation salt inside the shell into the electrolyte, the shell needs to contact the electrolyte. When the cation-supplementing material is added to the negative electrode coating, the probability of contacting the electrolyte is different at different positions of the negative electrode coating.

[0086] In order to facilitate the contact of cation-supplementing materials with the electrolyte, Figure 4As shown, the negative electrode plate 300 includes at least two layers of negative electrode coatings, at least one negative electrode coating 302 is arranged on the negative electrode current collector 301, and at least another negative electrode coating 303 is arranged on the side of the at least one negative electrode coating 302 away from the negative electrode current collector 301, so that the at least another negative electrode coating 303 is closer to the surface of the entire negative electrode coating, increasing the probability of contact with the electrolyte; and it is defined that the mass percentage of the cation-replenishing material in the at least one negative electrode coating 302 accounts for the mass percentage of the at least one negative electrode coating 302, and the mass percentage of the cation-replenishing material in the at least another negative electrode coating 303 accounts for the mass percentage of the at least another negative electrode coating 303, and W4 is satisfied. W4 is greater than W3, that is, the mass percentage of the cation-replenishing material in the at least two layers of negative electrode coatings is distributed in a concentration gradient; at this time, the mass percentage of the cation-replenishing material in the at least another negative electrode coating 303 is greater than the mass percentage of the cation-replenishing material in the at least one negative electrode coating 302, which helps the cation-replenishing material in the at least another negative electrode coating 303 to contact the electrolyte.

[0087] At the same time, after the cation-replenishing material is decomposed, it helps to improve the porosity of at least another negative electrode coating 303. The improvement of the porosity of at least another negative electrode coating 303 can further improve the wetting of the negative electrode coating with the electrolyte, so that the electrolyte infiltrates into at least one negative electrode coating 302, improves the contact of the cation-replenishing material in at least one negative electrode coating 302 with the electrolyte, and improves the contact between the cation-replenishing material in at least one negative electrode coating 302 and the electrolyte. In addition, the cation-replenishing material in at least two layers of negative electrode coatings is distributed in a gradient, which can extend the period of slow release of the cation-replenishing material and improve the battery cycle performance.

[0088] Optionally, the present application also provides a membrane, which includes the cation-supplementing material as described.

[0089] It is understandable that the cation-supplementing material can be prepared into a slurry and directly coated on the separator, or the material constituting the separator is mixed with the cation-supplementing material and the separator is prepared by melt extrusion so that the cation-supplementing material is coated in the separator material.

[0090] Optionally, the mass percentage of the cation-compensating material to the mass of the separator is 10% to 200%, preferably 50% to 100%.

[0091] Considering that if the mass of the cation-replenishing material inside the battery is insufficient, it is difficult to fully replenish cations in the middle and late stages of the battery cycle. At the same time, if the mass of the cation-replenishing material inside the battery is too much, the cations will be excessively replenished, making it difficult to further improve the cycle performance, and the mass energy density of the battery will also be reduced. Taking all factors into consideration, the mass percentage of the mass of the cation-replenishing material to the mass of the diaphragm is 10% to 200%, preferably 50% to 100%.

[0092] Optionally, the separator includes a first separator layer and a second separator layer provided on the first separator layer, and the second separator layer includes the cation-supplementing material.

[0093] like Figure 5 As shown, a diaphragm 200 according to an embodiment of the present application is shown. The diaphragm 200 includes a first diaphragm layer 201 and a second diaphragm layer 202 . The cation-supplementing material can be prepared into the second diaphragm layer 202 and disposed on the surface of the first diaphragm layer 201 .

[0094] Optionally, the thickness of the second diaphragm layer ranges from 100 nm to 10 μm, preferably from 1 μm to 5 μm;

[0095] And / or, the diaphragm is arranged on one side of the positive electrode sheet or the negative electrode sheet, and the second diaphragm layer is arranged on the side of the first diaphragm layer facing the negative electrode sheet.

[0096] Considering that the diaphragm needs to have a certain degree of air permeability to facilitate ion transmission, and the thickness of the diaphragm cannot be too large to reduce the thickness of the entire battery cell, after the battery cell is installed in the battery cell shell, it helps the battery cell have sufficient expansion space in the battery cell shell.

[0097] That is, if the thickness of the second diaphragm layer is too thick, the air permeability of the entire diaphragm will be reduced, affecting the penetration of the electrolyte into the diaphragm and the migration of ions between the diaphragms. At the same time, if the thickness of the second diaphragm layer is too thick, it will also occupy the volume of the battery cell and reduce the energy density. If the thickness of the second diaphragm layer is too thin, the quality of the cation-supplementing material will be reduced, which is not conducive to the subsequent replenishment of cations in the cycle.

[0098] Based on the above considerations, the thickness of the second diaphragm layer ranges from 100 nm to 10 μm, preferably from 1 μm to 5 μm.

[0099] In one embodiment, the diaphragm is used to be arranged on one side of the positive electrode plate or the negative electrode plate, for example, the diaphragm is arranged between the positive electrode plate and the negative electrode plate, or the diaphragm is arranged on the side of the negative electrode plate away from the positive electrode plate, and the second diaphragm layer is arranged on the side of the first diaphragm layer facing the negative electrode.

[0100] Taking lithium-ion batteries as an example, non-M element cation salts can be non-lithium salts. Considering that these non-lithium salts can electrostatically shield and inhibit the growth of lithium dendrites, which are generally produced at the negative electrode, it is preferred to coat the cation-supplementing material on the side of the diaphragm facing the negative electrode, that is, the second diaphragm layer is arranged on the side of the first diaphragm layer facing the negative electrode.

[0101] Alternatively, if Figure 6 As shown, the present application also provides a method for preparing a cation-supplementing material, comprising:

[0102] preparing a prepolymer emulsion for a shell layer;

[0103] The non-M element cation salt solution is added into the prepolymer emulsion of the shell layer, and the mixture is heated and stirred to obtain an ion-supplementing material.

[0104] Prepolymer is a substance formed by preliminary polymerization of monomers used to prepare the shell layer.

[0105] Prepolymer emulsion, the state in which the prepolymer is dispersed in water to form an emulsion.

[0106] In order to prepare a cationic supplementing material with a shell layer coated with a non-M element cationic salt, a prepolymer emulsion of the shell layer can be prepared, and a non-M element cationic salt solution is added to the prepolymer emulsion of the shell layer, heated and stirred to obtain an ion supplementing material. That is, the non-M element cationic salt solution is added to the prepolymer emulsion of the shell layer, and the prepolymer is further polymerized on the surface of the non-M element cationic salt to obtain a shell layer coated with a non-M element cationic salt. It can be understood that the non-M element cationic salt is added to an aqueous solution to obtain a non-M element cationic salt solution.

[0107] Optionally, the step of preparing the prepolymer emulsion of the shell layer includes: mixing the constituent monomers of the shell layer with a solvent, and heating to obtain the prepolymer emulsion of the shell layer.

[0108] Optionally, the step of mixing the monomers constituting the shell layer with a solvent and heating to obtain a prepolymer emulsion of the shell layer includes: mixing the monomers constituting the shell layer, amino resin monomers, formaldehyde substances, gelatin and water to obtain a mixed solution, adjusting the pH value of the obtained mixed solution to 6.0 to 8.5, heating to 40° C. to 70° C., and keeping the temperature for 20 min to 60 min to obtain the prepolymer emulsion of the shell layer;

[0109] The mass of the amino resin monomer is 20% to 70% of the mass of the non-M element cationic salt; the formaldehyde substance is 15% to 120% of the mass of the amino resin monomer; and the gelatin is 3% to 16% of the mass of the amino resin monomer.

[0110] For example, taking gelatin-modified amino resin as the shell layer, amino resin monomer, formaldehyde, gelatin and water are mixed, the pH value of the obtained mixed solution is adjusted to 6.0 to 8.5, heated to 40°C to 70°C, and kept warm for 20min to 60min to obtain a gelatin-modified amino resin prepolymer solution; an appropriate amount of non-M element cationic salt is added to the above gelatin-modified amino resin prepolymer solution, the temperature is raised to 40°C to 60°C, and the mixture is stirred thoroughly. The mixture is filtered and vacuum dried at 70°C to obtain a cation-supplementing material.

[0111] Optionally, the step of adding a non-M element cation salt solution to the prepolymer emulsion of the shell layer, heating and stirring to obtain a cation-supplementing material comprises:

[0112] Adding a non-M element cation salt solution to the prepolymer emulsion of the shell layer, stirring, heating to 40° C. to 60° C., filtering, and drying to obtain a first layer of shell coating material;

[0113] The mass ratio of the non-M element cation salt to the prepolymer emulsion of the shell layer is in the range of 1:100 to 1:1.

[0114] The non-M element cation salt solution is added to the prepolymer emulsion of the shell layer, and stirred to fully disperse the non-M element cation salt solution and the prepolymer emulsion of the shell layer, thereby improving the dispersibility of the non-M element cation salt solution, which is helpful for preparing a cation-supplementing material of a suitable size. The prepolymer is polymerized on the surface of the non-M element cation salt solution by heating to 40° C. to 60° C., and a shell layer is formed on the surface of the non-M element cation salt solution to coat the non-M element cation salt solution. The cation-supplementing material is obtained by filtering and drying.

[0115] Optionally, after the step of adding the non-M element cation salt solution to the prepolymer emulsion of the shell layer, stirring, heating to 40° C. to 60° C., filtering, and drying to obtain the first layer of shell coating material, the method further comprises:

[0116] The first layer shell coating material is mixed with the constituent monomers of the second layer shell and a solvent, an initiator is added, and the mixture is heated, stirred, and dried to obtain a cation-supplementing material;

[0117] The mass ratio of the first shell coating material to the second shell constituent monomers is in the range of 5% to 50%.

[0118] That is, in order to improve the coating property of the shell layer, a second shell layer is further provided on the surface of the first shell coating material.

[0119] Optionally, the step of mixing the first shell coating material with the monomers constituting the second shell and a solvent, adding an initiator, heating, stirring and drying to obtain the cation-supplementing material includes:

[0120] The first layer of shell coating material is mixed with butadiene, styrene and THF solvent, an initiator is added, and the mixture is heated, stirred and dried to obtain a cation-supplementing material;

[0121] Wherein, the mass ratio of the butadiene to the styrene ranges from 1:100 to 100:1.

[0122] That is, in one embodiment, styrene-butadiene rubber polymer can be used as the second shell layer. The styrene-butadiene rubber polymer as the second shell layer improves the density, toughness and heat resistance of the entire shell, thereby improving its thermal processing stability.

[0123] Optionally, the present application also provides a battery, the battery comprising the cation-supplementing material as described;

[0124] Or, comprising the electrolyte as described;

[0125] Or, comprising the positive electrode sheet as described;

[0126] Or, comprising the negative electrode sheet as described;

[0127] Or, comprising a diaphragm as described;

[0128] Alternatively, the cation-supplementing material comprises the cation-supplementing material obtained by the preparation method of the cation-supplementing material as described above.

[0129] The present application also provides an electrical device, which includes the battery as described above.

[0130] The present application coats the surface of the non-M element cation salt with a shell layer, which helps to reduce the release of the non-M element cation salt into the electrolyte during formation or the initial stage of circulation, so that the non-M element cation salt is released into the electrolyte in the middle and late stages of circulation, replenishing the cations consumed in the battery and improving the cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0131] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0132] Figure 1 is a schematic diagram of a cation-supplementing material according to one embodiment of the present application;

[0133] Figure 2 is a schematic diagram of a cation-supplementing material according to another embodiment of the present application;

[0134] Figure 3 is a schematic diagram of a positive electrode sheet according to an embodiment of the present application;

[0135] Figure 4 is a schematic diagram of a negative electrode sheet according to an embodiment of the present application;

[0136] Figure 5 is a schematic diagram of a diaphragm according to an embodiment of the present application;

[0137] Figure 6 This is a schematic flow chart of a method for preparing a cation-supplementing material according to one embodiment of the present application;

[0138] Figure 7 is a schematic diagram of a battery cell according to an embodiment of the present application;

[0139] Figure 8 yes Figure 7 An exploded view of a battery cell according to an embodiment of the present application is shown;

[0140] Fig. 9 is a schematic diagram of a battery module according to an embodiment of the present application;

[0141] Fig.10 is a schematic diagram of a battery pack according to an embodiment of the present application;

[0142] Fig.11 yes Fig.10 An exploded view of a battery pack according to an embodiment of the present application is shown;

[0143] Fig.12 It is a schematic diagram of an electrical device using a battery cell according to an embodiment of the present application as a power source.

[0144] Description of Figure Numbers:

[0145]

[0146]

[0147] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0148] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0149] Hereinafter, the embodiments of the electrolyte additive, electrolyte, electrode assembly, battery and electrical device of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0150] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0151] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0152] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0153] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0154] With the rapid growth of portable electronic devices and electric vehicles, the demand for power batteries is also growing. Among them, the electrochemical performance of batteries is also attracting more and more attention.

[0155] Due to some irreversible reactions such as the formation of the solid electrolyte membrane (SEI membrane) on the surface of the negative electrode during the initial charge and discharge formation process, the positive electrode material will experience ion loss. Taking lithium-ion batteries as an example, in the prior art, in order to solve the above problem, a lithium supplement is added to the battery. The lithium supplement is used to supplement the lithium ions lost during the initial formation process.

[0156] Taking into account the phenomenon of cation loss during the battery cycle, the cation loss phenomenon occurs not only in the formation process, but also in the cycle process. In particular, as the cycle proceeds, the cations are continuously consumed. In the middle and late stages of the battery cycle, the lack of cations will lead to a decline in the battery cycle performance.

[0157] For example, during the cycle, due to SEI film consumption, electrolyte decomposition and other reasons, the added potassium salt or sodium salt will be gradually consumed in the early cycle, and deposited on the negative electrode in the form of salt or dead metal elements, losing its improvement function for long-term cycles, especially in the later stages of the cycle.

[0158] In order to solve the above problems, the present application proposes a cation supplement material for use in M ​​element batteries, comprising a shell layer and a core material disposed in the shell layer, wherein the core material comprises a non-M element cation salt. The shell layer and the core material disposed in the shell layer refer to the core material being located inside the shell layer, such as Figure 1 , which is a schematic structural diagram of a cation-supplementing material, the surface of a core material 10 is coated with a shell layer 20 .

[0159] The core material is encapsulated in the shell layer, and the core material includes a non-M element cation salt, which helps to reduce the release of the non-M element cation salt into the electrolyte during formation or the initial stage of circulation, so that the non-M element cation salt is released into the electrolyte in the middle and late stages of the cycle, replenishing the cations consumed in the battery and improving the cycle performance of the battery.

[0160] It is understandable that these non-M element cation salts can participate in the formation of the SEI film. For example, taking a lithium-ion battery as an example, that is, the M element battery is a lithium-ion battery, and the non-M element cation salt is a non-lithium salt, such as sodium salt, magnesium salt, etc. These non-M element cation salts (such as sodium salt, magnesium salt) can be deposited on the surface of the negative electrode to repair the SEI film; in addition, the non-M element cation salt can also play the role of electrostatic shielding and inhibit the growth of lithium dendrites. Since the above-mentioned non-lithium salts can be dissolved into the electrolyte in the middle and late stages of the cycle, they have a significant effect on the improvement of the battery cycle in the middle and late stages.

[0161] It is understandable that the above-mentioned cation-supplementing materials can be applied to lithium batteries or sodium batteries, and can be applied to suitable batteries as needed.

[0162] In one embodiment, the non-M element cation in the non-M element cation salt includes at least one of a Group IA element cation or a Group IIA element cation.

[0163] It is understandable that information on Group IA elements and Group IIA elements can be obtained from the periodic table. For example, Group IA elements include sodium, potassium, etc., and Group IIA elements include calcium, magnesium, etc.

[0164] In one embodiment, the M element battery comprises a lithium battery, and the non-M element cations in the non-M element cation salt comprise one or more of potassium ions, sodium ions, barium ions, cesium ions, rubidium ions, and calcium ions; or, the M element battery comprises a sodium battery, and the non-M element cations in the non-M element cation salt comprise one or more of potassium ions, lithium ions, barium ions, cesium ions, rubidium ions, and calcium ions.

[0165] It can be understood that the M element battery of the present application includes but is not limited to a lithium battery or a sodium battery.

[0166] The M element battery includes a lithium battery, and the non-M element cations in the non-M element cation salt include but are not limited to one or more of potassium ions, sodium ions, barium ions, cesium ions, rubidium ions and calcium ions.

[0167] The M element battery includes a sodium battery, and the non-M element cations in the non-M element cation salt include but are not limited to one or more of potassium ions, lithium ions, barium ions, cesium ions, rubidium ions and calcium ions.

[0168] It is understandable that when the M element battery is a lithium battery, the non-M element cation salt includes a non-lithium salt. Considering that for lithium-ion batteries, the price of lithium salts is often relatively expensive, which increases the cost of the battery. For this reason, non-lithium salts are used to supplement cations, thereby improving the battery cycle performance and reducing costs.

[0169] In one embodiment, the anion in the non-M element cation salt includes at least one of perchlorate, tetrafluoroborate, hexafluoroarsenate, hexafluorophosphate, bis(trifluoromethylsulfonyl)imide, difluorophosphate, bis(difluorosulfonyl)imide, bis(oxalatoborate) and difluorooxalatoborate, nitrate, sulfate, sulfite, and trifluoromethanesulfonyl.

[0170] It is understood that the anions in the non-M element cation salt include but are not limited to at least one of perchlorate, tetrafluoroborate, hexafluoroarsenate, hexafluorophosphate, bistrifluoromethylsulfonyl imide, difluorophosphate, bisdifluorosulfonyl imide, bisoxalate borate and difluorooxalate borate, nitrate, sulfate, sulfite, and trifluoromethanesulfonyl.

[0171] Considering that the anions in the non-M element cation salts in the common electrolytes of the above anions include the above anions, the applicability of the non-M element cation salts in batteries can be improved. In addition, the salts composed of the above anions and the non-M element cations can be effectively dissolved in the electrolyte.

[0172] In one embodiment, the mass percentage of the non-M element cation salt to the mass of the cation-supplementing material is 50% to 99%, preferably 70% to 95%.

[0173] In order to effectively encapsulate the core material in the shell layer and to have a shell layer of suitable thickness, the mass percentage of the non-M element cation salt to the mass of the cation-supplementing material is 50% to 99%, preferably 70% to 95%.

[0174] In the above 50% to 99%, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 99%, etc., as well as the range values ​​between any two of the above point values.

[0175] In the above 70% to 95%, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 70%, 75%, 80%, 85%, 90%, 95%, etc., and the range values ​​between any two of the above point values.

[0176] In one embodiment, the Dv50 value of the cation-supplementing material is in the range of 100 nm to 10 μm, preferably, 200 nm to 2 μm.

[0177] Dv50 is the particle size corresponding to when the cumulative particle size distribution percentage of a sample reaches 50%. Its physical meaning is that particles with a particle size larger than it account for 50%, and particles with a particle size smaller than it also account for 50%. Dv50 is also called the median diameter or median particle size. Dv50 is often used to indicate the average particle size of powders.

[0178] Among the sample particles, 50% of the total volume of the particles have a particle size larger than this value, and another 50% of the total volume of the particles have a particle size smaller than this value; Dv50 can represent the median particle size of the sample.

[0179] Dv50 can be tested by methods known in the art. For example, GB / T19077-2016 can be referred to, and a Malvern laser particle size analyzer can be used for characterization testing, such as a Malvern Mastersizer-3000 or other instrument.

[0180] If the Dv50 of the cation-supplementing material is too small, the coating property of the shell is poor and it is difficult to form a coating state; if the Dv50 of the cation-supplementing material is too large, when the cation-supplementing material is set on the positive electrode plate or the negative electrode plate, after the cation-supplementing material is decomposed, larger pores will be left in the positive electrode coating or the negative electrode coating, the mechanical properties of the plate will be reduced, and the coating will easily collapse and break. When the cation-supplementing material is prepared into a slurry and applied to the diaphragm, if the Dv50 of the cation-supplementing material is too large, it is difficult to obtain a cation-supplementing material coating of suitable thickness. When the cation-supplementing material is added to the electrolyte, if the Dv50 of the cation-supplementing material is too small, the pores of the plate or the diaphragm may be blocked during formation or the initial stage of circulation. If the Dv50 of the cation-supplementing material is too large, it may hinder the electrolyte from wetting the plate or the diaphragm.

[0181] Therefore, taking all factors into consideration, the Dv50 range of the cation-supplementing material is 100 nm to 10 μm, preferably 200 nm to 2 μm.

[0182] In the above-mentioned 100nm to 10μm, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 100nm, 200nm, 500nm, 800nm, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, etc., as well as the range values ​​between any two of the above-mentioned point values.

[0183] In the above-mentioned 200nm to 2μm, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1μm, 1.5μm, 2μm, etc., as well as the range values ​​between any two of the above-mentioned point values.

[0184] In one embodiment, the thickness of the shell layer ranges from 20 nm to 800 nm, preferably from 50 nm to 200 nm; and / or the shell layer completely covers the surface of the core material.

[0185] Considering that the wall thickness of the shell layer has an impact on the cation-supplementing material and the cation replenishment in the middle and late stages of the cycle, for example, when the shell layer is at a certain thickness, the longer the period of release of the non-M element cation salt in the cation-supplementing material into the electrolyte, the more continuously the cations can be replenished, and the cycle performance will be improved. However, when the thickness of the shell layer is too thick, the shell layer is difficult to be swollen by the solvent in the electrolyte or etched by the acid, which is not conducive to the release of the non-M element cation salt. For example, in the worst case, when the cycle life of the battery reaches the end, the non-M element cation salt is released into the electrolyte to replenish the cations, and it is difficult to improve the performance of the battery at this time. For this reason, based on comprehensive considerations, the thickness range of the shell layer is 20nm to 800nm, preferably 50nm to 200nm.

[0186] In the above-mentioned 20nm to 800nm, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 20nm, 30nm, 50nm, 80nm, 100nm, 120nm, 150nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, etc., and the range values ​​between any two of the above-mentioned point values.

[0187] In the above-mentioned 250nm to 200nm, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 120nm, 135nm, 150nm, 170nm, 200nm, etc., and the range values ​​between any two of the above-mentioned point values.

[0188] It can also be understood that, in theory, the non-M element cation salt in the shell layer in the present application can be solid or liquid. Preferably, the non-M element cation salt in the shell layer in the present application can be solid (it can be understood that a drying step will be performed during the preparation of the cation-supplementing material, and the non-M element cation salt solution coated in the shell layer will be dried during the drying process.). On the one hand, the solid non-M element cation salt in the shell layer occupies less space than the liquid non-M element cation salt solution, which is conducive to the preparation of small-sized cation-supplementing materials. At the same time, the mass of the solvent in the non-M element cation salt solution can also be subtracted, thereby reducing the overall mass of the cation-supplementing material. When the cation-supplementing material is added to the battery, it helps to improve the energy density of the battery.

[0189] In addition, the solid state has mechanical strength compared to the liquid state. During the extrusion process of the positive electrode sheet, the negative electrode sheet and the diaphragm, the cation-supplementing material is not easily crushed or broken. It is difficult for the shell of the cation-supplementing material to be damaged due to the extrusion process during the preparation process, thereby reducing the direct release of non-M element cation salts in the shell and improving the subsequent cation replenishment in the battery cycle.

[0190] In one embodiment, the shell layer completely covers the surface of the core material.

[0191] Full coverage means that the shell layer is continuously covered on the surface of the core material, and the surface of the core material is not exposed.

[0192] In order to reduce the exposure of the core material to the electrolyte during the formation process or the early stage of the cycle, it is preferred that the shell layer completely covers the surface of the core material. In this way, the shell layer is etched by the acidic substances (such as HF) generated during the battery cycle, or the shell layer is swollen by immersion in the electrolyte to form pores, thereby slowly exposing the core material, which is helpful for the replenishment of cations in the middle and late stages of the cycle.

[0193] In one embodiment, the material of the shell layer includes at least one of a gelatin-modified amino resin composite material, a styrene-butadiene rubber polymer, and an acrylate polymer.

[0194] It is understandable that the material of the shell layer includes but is not limited to at least one of a gelatin-modified amino resin composite material, a styrene-butadiene rubber polymer, and an acrylate polymer.

[0195] Gelatin is a peptide molecule polymer and a multi-level hydrolysis product of collagen. Its molecular formula is AlH 3 KO 8 S 2 .

[0196] Amino resin is a general term for resins formed by condensation of amino-containing compounds and formaldehyde.

[0197] Styrene butadiene rubber, also known as polystyrene butadiene copolymer, can be copolymerized by monomers such as styrene and butadiene.

[0198] Acrylate polymer, during the polymerization process, the monomers include acrylate monomers, for example, acrylonitrile, methyl methacrylate, azobisisobutyronitrile, triallyl isocyanurate are mixed and heated to react to obtain the acrylate polymer.

[0199] For example, gelatin-modified amino resin is used as the shell layer, wherein gelatin has good coating and etching properties, and the addition of amino resin can enhance the mechanical properties of gelatin, so the two form a composite shell layer, improving the functionality and mechanical properties of the shell layer.

[0200] The shell layer is used to slow down the release rate of the non-M element cation salt inside the shell layer. Specifically, during the early cycle of the battery, due to the coating effect of the shell layer, the internal non-M element cation salt is difficult to be dissolved into the electrolyte for cation replenishment. During the long-term cycle process, the electrolyte will produce trace acidic substances, which will gradually etch the surface of the shell layer (for example, gelatin-modified amino resin), and then the non-M element cation salt inside the shell layer will gradually be exposed and dissolved in the electrolyte, which can play a good role in long-term cyclic cation replenishment.

[0201] It can also be understood that, in addition to being etched by the acidic substances in the electrolyte, the shell layer can also utilize the shell layer material (such as polyurea resin) to swell under long-term immersion in the electrolyte to form a porous structure. The non-M element cation salt in the shell layer is gradually exposed from the porous position, contacts with the electrolyte, and dissolves in the electrolyte, which can play a good role in long-term cyclic cation replenishment.

[0202] In one embodiment, the shell layer includes at least two shell layers, at least one shell layer is arranged on the surface of the core material, and at least another shell layer is arranged on the side of the at least one shell layer away from the core material; the thickness range of at least one shell layer is 10nm to 400nm, preferably, 30nm to 150nm; the thickness range of at least another shell layer is 10nm to 400nm, preferably, 30nm to 150nm.

[0203] In order to improve the coating effect of the shell layer on the core material, at least two layers of shell are used, for example, two layers, three layers, etc. Figure 2 As shown, the shell 20 includes a shell 21 and another side shell 22.

[0204] It is understandable that, since non-M element cation salts are easily soluble in electrolyte, the shell layer needs to have good coating properties to isolate the electrolyte; at the same time, in order to play a role of sustained release in the middle and late stages of the cycle, the shell also needs to have the characteristics of being etched by acid (such as HF) or being swollen by the electrolyte to produce pores. In addition, in order to ensure the completeness of the shell, it also needs to have good mechanical properties.

[0205] Based on the above requirements, a single-component shell is difficult to meet the requirements of coating, etching, mechanical strength, porosity, etc. For example, a single-component gelatin shell has coating and etching properties, but poor mechanical properties, and a single-component styrene-butadiene rubber has good mechanical properties, but its coating properties are poor.

[0206] For example, in the structure of the two-layer shell, the present application uses gelatin-modified amino resin composite material as the first layer shell to provide good coating and etchability; styrene-butadiene rubber polymer is used as the second layer shell to improve the compactness, toughness and heat resistance of the shell, thereby improving its thermal processing stability. The combination of the two plays a role in taking advantage of each other's strengths and making up for each other's weaknesses.

[0207] Furthermore, in order to ensure that each shell has good coating properties and can also be etched or swelled under the action of the electrolyte in the middle and late stages of the battery cycle to release the non-M element cation salt into the electrolyte, the thickness of at least one shell layer ranges from 10 nm to 400 nm, preferably, from 30 nm to 150 nm; the thickness of at least another shell layer ranges from 10 nm to 400 nm, preferably, from 30 nm to 150 nm.

[0208] In the above-mentioned 10nm to 400nm, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 10nm, 25nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 120nm, 135nm, 150nm, 170nm, 200nm, 250nm, 300nm, 35nm, 400nm, etc., and the range values ​​between any two of the above-mentioned point values.

[0209] In the above-mentioned 30nm to 150nm, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 30nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 120nm, 135nm, 150nm, etc., and the range values ​​between any two of the above-mentioned point values.

[0210] In one embodiment, the material of at least one shell layer includes a gelatin-modified amino resin composite material; and / or the material of at least another shell layer includes at least one of a styrene-butadiene rubber polymer and an acrylate polymer.

[0211] It is understandable that the material of at least one shell layer includes but is not limited to gelatin-modified amino resin composite material; the material of at least another shell layer includes but is not limited to at least one of styrene-butadiene rubber polymer and acrylate polymer.

[0212] In one embodiment, the present application further provides an electrolyte, which includes the cation-supplementing material as described above.

[0213] By directly adding the cation-replenishing material into the electrolyte, the non-M element cation salt in the shell can be slowly exposed during the battery cycle, so that the non-M element cation salt dissolves in the electrolyte, which can play a good role in long-term cyclic cation replenishment.

[0214] For example, it is understandable that in the early cycle, due to the coating effect of the shell layer, the non-M element cation salt inside cannot overflow and dissolve. In the long-term cycle process, the electrolyte will produce trace acidic substances, which will gradually etch the surface of the microshell layer, and then the non-M element cation salt inside the shell layer will gradually be exposed and dissolved in the electrolyte.

[0215] In one embodiment, the mass percentage of the cation-supplementing material to the mass of the electrolyte is 1% to 100%, preferably, 5% to 20%.

[0216] Considering that if the mass of the cation-replenishing material inside the battery is insufficient, it is difficult to fully replenish cations in the middle and late stages of the battery cycle. At the same time, if the mass of the cation-replenishing material inside the battery is too much, the cations will be excessively replenished, making it difficult to further improve the cycle performance, and the mass energy density of the battery will also be reduced. Therefore, when the cation-replenishing material is directly added to the electrolyte, the mass percentage of the mass of the cation-replenishing material to the mass of the electrolyte ranges from 1% to 100%, preferably, 5% to 20%. Define the mass of the electrolyte without the addition of the cation-replenishing material as m1, and the mass of the cation-replenishing material used to be added to the electrolyte as m2, then the mass percentage calculation formula of the mass of the cation-replenishing material to the mass of the electrolyte is m2 / m1×100%.

[0217] In the above 1% to 100%, the values ​​include the minimum and maximum values ​​of the range, and every value between such minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 1%, 0.1%, 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 60%, 70%, 80%, 90%, 100%, etc., as well as the range values ​​between any two of the above point values.

[0218] In the above 5% to 20%, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, etc., and the range values ​​between any two of the above point values.

[0219] In one embodiment, the mass percentage of the non-M element cation salt in the cation-supplementing material to the total mass of the electrolyte is 0.0001% to 50%, preferably, 0.5% to 10%.

[0220] It is understandable that when the cation-replenishing material is added to the electrolyte, the mass percentage of the non-M element cation salt in the added cation-replenishing material to the total mass of the electrolyte is 0.0001% to 50%, preferably 0.5% to 10%. In this way, it helps to improve the cycle performance of the battery. The total mass of the electrolyte is defined as m14 (including the mass of the cation-replenishing material), and the mass of the non-M element cation salt in the cation-replenishing material added to the electrolyte is m15. The mass percentage calculation formula of the mass of the cation-replenishing material to the mass of the electrolyte is m15 / m14×100%.

[0221] In the above 0.0001% to 50%, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 0.0001%, 0.001%, 0.01%, 0.1%, 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, etc., and the range values ​​between any two of the above point values.

[0222] In the above 0.5% to 10%, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 0.5%, 0.8%, 1%, 1.5%, 3%, 3.5%, 4.5%, 5%, 6%, 7%, 8%, 9%, 10%, etc., as well as the range values ​​between any two of the above point values.

[0223] In one embodiment, the electrolyte includes a lithium salt, and the lithium salt includes at least one of lithium perchlorate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium difluorophosphate, lithium bis(difluorosulfonyl)imide, lithium bis(oxalatoborate), lithium difluorooxalatoborate, and lithium trifluoromethanesulfonyl; and / or, the electrolyte includes a solvent, and the solvent includes at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and fluoroethylene carbonate.

[0224] When the battery is a lithium battery, the electrolyte includes a lithium salt, and the lithium salt includes but is not limited to at least one of lithium perchlorate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium difluorophosphate, lithium bis(difluorosulfonyl)imide, lithium bis(oxalatoborate), lithium difluorooxalatoborate, and lithium trifluoromethanesulfonyl.

[0225] The electrolyte includes a solvent, and the solvent includes but is not limited to at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and fluoroethylene carbonate.

[0226] In one embodiment, the present application further provides a positive electrode plate, which includes the cation-supplementing material as described above.

[0227] It is understandable that the cation-supplementing material can be added inside the positive electrode coating or disposed on the surface of the positive electrode coating.

[0228] In one embodiment, the positive electrode plate includes a positive electrode current collector and a positive electrode coating disposed on the positive electrode current collector, and the mass percentage of the cation-supplementing material to the total mass of the positive electrode coating is 0.5% to 20%, preferably 1% to 5%.

[0229] On the one hand, if the mass of the cation-replenishing material inside the battery is insufficient, it will be difficult to sufficiently replenish cations in the middle and late stages of the battery cycle. At the same time, if the mass of the cation-replenishing material inside the battery is too much, there will be excessive cation replenishment, making it difficult to further improve the cycle performance, and at the same time reducing the mass energy density of the battery.

[0230] On the other hand, considering that non-M element cation salts will dissolve into the electrolyte during the cycle, leaving pores in the positive electrode coating, if too much cation-supplementing material is added to the positive electrode coating, the porosity of the positive electrode coating in the later stage of the cycle will be increased. If the porosity is too high, although the wettability of the positive electrode coating to the electrolyte can be improved, the mechanical strength of the positive electrode coating decreases, and the positive electrode coating is prone to collapse and rupture. Therefore, considering comprehensively, the mass percentage of the mass of the cation-supplementing material to the total mass of the positive electrode coating ranges from 0.5% to 20%, preferably, 1% to 5%. Define the mass of the cation-supplementing material not added to the positive electrode coating as m3, and the mass of the cation-supplementing material used to be added to the positive electrode coating as m4, then the mass percentage of the mass of the cation-supplementing material to the total mass of the positive electrode coating is calculated as m4 / (m3+m4)×100%.

[0231] In the above 0.5% to 20%, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 0.5%, 0.8%, 1%, 1.5%, 3%, 3.5%, 4.5%, 5%, 6%, 7%, 8%, 9%, 10%, 12%, 15%, 18%, 20%, etc., and the range values ​​between any two of the above point values.

[0232] In the above 1% to 5%, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 1%, 1.5%, 2%, 3%, 3.5%, 4%, 4.5%, 5%, etc., and the range values ​​between any two of the above point values.

[0233] In one embodiment, the positive electrode coating includes a binder, and the mass percentage of the binder in the positive electrode coating to the total mass of the positive electrode coating is 0.5% to 10%, preferably 1% to 3%.

[0234] Considering that the shell of the cation-supplementing material has adhesive properties, when the cation-supplementing material is added to the positive electrode coating, the amount of the binder added to the positive electrode coating can be reduced accordingly. For this reason, the mass percentage of the binder in the positive electrode coating to the total mass of the positive electrode coating is 0.5% to 10%, preferably 1% to 3%. The total mass of the positive electrode coating is defined as m5 (including the mass of the binder, wherein the mass of the binder is m6), and the mass percentage of the binder to the total mass of the positive electrode coating is calculated as m6 / m5×100%.

[0235] In the above 0.5% to 10%, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 0.5%, 1%, 1.5%, 2%, 3%, 3.5%, 4%, 4.5%, 5%, 6%, 7%, 8%, 9%, 10%, etc., as well as the range values ​​between any two of the above point values.

[0236] In the above 1% to 3%, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 1%, 1.5%, 2%, 3%, etc., and the range values ​​between any two of the above point values.

[0237] In one embodiment, the positive electrode plate includes a positive electrode current collector and at least two layers of positive electrode coatings disposed on the positive electrode current collector, at least one positive electrode coating is disposed on the positive electrode current collector, and at least another positive electrode coating is disposed on the side of the at least one positive electrode coating away from the positive electrode current collector. It is defined that the mass percentage of the cation-replenishing material in the at least one positive electrode coating to the mass percentage of the at least one positive electrode coating is W1, and the mass percentage of the cation-replenishing material in the at least another positive electrode coating to the mass percentage of the at least another positive electrode coating is W2, satisfying that W2 is greater than W1.

[0238] It is understandable that in order to facilitate the shell damage and effectively dissolve the non-M element cation salt inside the shell into the electrolyte, the shell needs to contact the electrolyte. When the cation supplement material is added to the positive electrode coating, the probability of contacting the electrolyte is different at different positions of the positive electrode coating.

[0239] In order to facilitate the contact of cation-supplementing materials with the electrolyte, Figure 3 As shown, the positive electrode plate 100 includes at least two layers of positive electrode coatings, at least one positive electrode coating 102 is arranged on the positive electrode current collector 101, and at least another positive electrode coating 103 is arranged on the side of the at least one positive electrode coating 102 away from the positive electrode current collector 101, so that the at least another positive electrode coating 103 is closer to the surface of the entire positive electrode coating, increasing the probability of contact with the electrolyte; and it is defined that the mass percentage of the cation-replenishing material in the at least one positive electrode coating 102 to the mass percentage of the at least one positive electrode coating 102 is W1, and the mass percentage of the cation-replenishing material in the at least another positive electrode coating 103 to the mass percentage of the at least another positive electrode coating 103 is W2, satisfying that W2 is greater than W1, that is, the mass percentage of the cation-replenishing material in the at least two layers of positive electrode coatings is distributed in a concentration gradient; at this time, the mass percentage of the cation-replenishing material in the at least another positive electrode coating 103 is greater than the mass percentage of the cation-replenishing material in the at least one positive electrode coating 102, which helps the cation-replenishing material in the at least another positive electrode coating 103 to contact the electrolyte.

[0240] At the same time, after the cation-replenishing material is decomposed, it helps to improve the porosity of the at least another positive electrode coating 103. The improvement of the porosity of the at least another positive electrode coating 103 can further improve the wetting of the positive electrode coating with the electrolyte, so that the electrolyte infiltrates into at least one positive electrode coating 102, improves the contact of the cation-replenishing material in at least one positive electrode coating 102 with the electrolyte, and improves the contact between the cation-replenishing material in at least one positive electrode coating 102 and the electrolyte. In addition, the cation-replenishing material in at least two layers of positive electrode coatings is distributed in a gradient, which can extend the period of slow release of the cation-replenishing material and improve the battery cycle performance.

[0241] In one embodiment, the present application further provides a negative electrode plate, which includes the cation-supplementing material as described above.

[0242] It is understandable that, taking lithium-ion batteries as an example, considering that lithium dendrites are mainly generated at the negative electrode, cation-supplementing materials are added to the negative electrode coating so that after the cations are released, they are first at the negative electrode, and the electrostatic shielding effect of the cations is utilized to inhibit the growth of lithium dendrites.

[0243] In one embodiment, the negative electrode plate includes a negative electrode current collector and a negative electrode coating disposed on the negative electrode current collector, and the mass percentage of the cation-supplementing material to the total mass of the negative electrode coating is 0.5% to 40%, preferably 1% to 5%.

[0244] On the one hand, if the mass of the cation-replenishing material inside the battery is insufficient, it will be difficult to sufficiently replenish cations in the middle and late stages of the battery cycle. At the same time, if the mass of the cation-replenishing material inside the battery is too much, there will be excessive cation replenishment, making it difficult to further improve the cycle performance, and at the same time reducing the mass energy density of the battery.

[0245] On the other hand, considering that non-M element cation salts will dissolve into the electrolyte during the cycle, leaving pores in the negative electrode coating, if too much cation-supplementing material is added to the negative electrode coating, the porosity of the negative electrode coating will be increased in the later stage of the cycle. If the porosity is too high, the mechanical strength of the negative electrode coating will decrease, and the negative electrode coating will be prone to collapse and rupture. Therefore, considering comprehensively, the mass percentage of the mass of the cation-supplementing material to the total mass of the negative electrode coating ranges from 0.5% to 40%, preferably, 1% to 5%. Define the mass of the negative electrode coating without the addition of cation-supplementing material as m7, and the mass of the cation-supplementing material added to the negative electrode coating as m8, then the mass percentage of the mass of the cation-supplementing material to the total mass of the positive electrode coating is calculated as m8 / (m7+m8)×100%.

[0246] In the above 0.5% to 40%, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 0.5%, 0.8%, 1%, 1.5%, 3%, 3.5%, 4.5%, 5%, 6%, 7%, 8%, 9%, 10%, 12%, 15%, 18%, 20%, 25%, 30%, 34%, 40%, etc., and the range values ​​between any two of the above point values.

[0247] In the above 1% to 5%, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 0.5%, 1%, 1.5%, 3%, 3.5%, 4.5%, 5%, and the range values ​​between any two of the above point values.

[0248] In one embodiment, the negative electrode coating includes a binder, and the mass percentage of the binder in the negative electrode coating to the total mass of the negative electrode coating is 0.5% to 15%, preferably 1% to 5%.

[0249] Considering that the shell of the cation-supplementing material has adhesive properties, when the cation-supplementing material is added to the negative electrode coating, the amount of the binder added to the negative electrode coating can be reduced accordingly, and the mass percentage of the binder in the negative electrode coating to the total mass of the negative electrode coating is 0.5% to 15%, preferably 1% to 5%. The total mass of the negative electrode coating is defined as m9 (including the mass of the binder, wherein the mass of the binder is m10), and the mass percentage of the binder to the total mass of the negative electrode coating is calculated as m10 / m9×100%.

[0250] In the above-mentioned 0.5% to 15%, the values ​​include the minimum and maximum values ​​of the range, and every value between such minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 0.5%, 1%, 1.5%, 2%, 3%, 3.5%, 4%, 4.5%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, etc., as well as the range values ​​between any two of the above-mentioned point values.

[0251] In the above 1% to 5%, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 1%, 1.5%, 2%, 3%, 4%, 5%, etc., and the range values ​​between any two of the above point values.

[0252] In one embodiment, the negative electrode plate includes a negative electrode current collector and at least two layers of negative electrode coatings disposed on the negative electrode current collector, at least one negative electrode coating is disposed on the negative electrode current collector, and at least another negative electrode coating is disposed on the side of the at least one negative electrode coating away from the negative electrode current collector. It is defined that the mass percentage of the cation-replenishing material in the at least one negative electrode coating is W3, and the mass percentage of the cation-replenishing material in the at least another negative electrode coating is W4, satisfying that W4 is greater than W3.

[0253] It is understandable that in order to facilitate the shell damage and effectively dissolve the non-M element cation salt inside the shell into the electrolyte, the shell needs to contact the electrolyte. When the cation-supplementing material is added to the negative electrode coating, the probability of contacting the electrolyte is different at different positions of the negative electrode coating.

[0254] In order to facilitate the contact of cation-supplementing materials with the electrolyte, Figure 4As shown, the negative electrode plate 300 includes at least two layers of negative electrode coatings, at least one negative electrode coating 302 is arranged on the negative electrode current collector 301, and at least another negative electrode coating 303 is arranged on the side of the at least one negative electrode coating 302 away from the negative electrode current collector 301, so that the at least another negative electrode coating 303 is closer to the surface of the entire negative electrode coating, increasing the probability of contact with the electrolyte; and it is defined that the mass percentage of the cation-replenishing material in the at least one negative electrode coating 302 accounts for the mass percentage of the at least one negative electrode coating 302, and the mass percentage of the cation-replenishing material in the at least another negative electrode coating 303 accounts for the mass percentage of the at least another negative electrode coating 303, and W4 is satisfied. W4 is greater than W3, that is, the mass percentage of the cation-replenishing material in the at least two layers of negative electrode coatings is distributed in a concentration gradient; at this time, the mass percentage of the cation-replenishing material in the at least another negative electrode coating 303 is greater than the mass percentage of the cation-replenishing material in the at least one negative electrode coating 302, which helps the cation-replenishing material in the at least another negative electrode coating 303 to contact the electrolyte.

[0255] At the same time, after the cation-replenishing material is decomposed, it helps to improve the porosity of at least another negative electrode coating 303. The improvement of the porosity of at least another negative electrode coating 303 can further improve the wetting of the negative electrode coating with the electrolyte, so that the electrolyte infiltrates into at least one negative electrode coating 302, improves the contact of the cation-replenishing material in at least one negative electrode coating 302 with the electrolyte, and improves the contact between the cation-replenishing material in at least one negative electrode coating 302 and the electrolyte. In addition, the cation-replenishing material in at least two layers of negative electrode coatings is distributed in a gradient, which can extend the period of slow release of the cation-replenishing material and improve the battery cycle performance.

[0256] In one embodiment, the present application also provides a membrane, which includes the cation-supplementing material as described above.

[0257] It is understandable that the cation-supplementing material can be prepared into a slurry and directly coated on the separator, or the material constituting the separator is mixed with the cation-supplementing material and the separator is prepared by melt extrusion so that the cation-supplementing material is coated in the separator material.

[0258] In one embodiment, the mass percentage of the cation-compensating material to the mass of the separator is 10% to 200%, preferably 50% to 100%.

[0259] Considering that if the mass of the cation-replenishing material inside the battery is not enough, it will be difficult to fully replenish cations in the middle and late stages of the battery cycle. At the same time, if the mass of the cation-replenishing material inside the battery is too much, the cations will be excessively replenished, making it difficult to further improve the cycle performance, and the mass energy density of the battery will also be reduced. Taking all factors into consideration, the mass percentage of the mass of the cation-replenishing material to the mass of the diaphragm is 10% to 200%, preferably 50% to 100%. Define the mass of the cation-replenishing material not added to the diaphragm as m12, and the mass of the cation-replenishing material added to the diaphragm as m13. The mass percentage calculation formula of the mass of the cation-replenishing material to the mass of the diaphragm is m13 / m12×100%.

[0260] In the above 10% to 200%, the values ​​include the minimum and maximum values ​​of the range, and every value between such minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 100%, 120%, 140%, 160%, 180%, 200%, etc., and the range values ​​between any two of the above point values.

[0261] In the above 50% to 100%, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 100%, etc., as well as the range values ​​between any two of the above point values.

[0262] In one embodiment, the separator includes a first separator layer and a second separator layer disposed on the first separator layer, and the second separator layer includes a cation-compensating material.

[0263] like Figure 5 As shown, a diaphragm 200 according to an embodiment of the present application is shown. The diaphragm 200 includes a first diaphragm layer 201 and a second diaphragm layer 202 . The cation-supplementing material can be prepared into the second diaphragm layer 202 and disposed on the surface of the first diaphragm layer 201 .

[0264] In one embodiment, the thickness of the second diaphragm layer ranges from 100 nm to 10 μm, preferably from 1 μm to 5 μm; and / or, the diaphragm is arranged on one side of the positive electrode sheet or the negative electrode sheet, and the second diaphragm layer is arranged on the side of the first diaphragm layer facing the negative electrode sheet.

[0265] Considering that the diaphragm needs to have a certain degree of air permeability to facilitate ion transmission, and the thickness of the diaphragm cannot be too large to reduce the thickness of the entire battery cell, after the battery cell is installed in the battery cell shell, it helps the battery cell have sufficient expansion space in the battery cell shell.

[0266] That is, if the thickness of the second diaphragm layer is too thick, the air permeability of the entire diaphragm will be reduced, affecting the penetration of the electrolyte into the diaphragm and the migration of ions between the diaphragms. At the same time, if the thickness of the second diaphragm layer is too thick, it will also occupy the volume of the battery cell and reduce the energy density. If the thickness of the second diaphragm layer is too thin, the quality of the cation-supplementing material will be reduced, which is not conducive to the subsequent replenishment of cations in the cycle.

[0267] Based on the above considerations, the thickness of the second diaphragm layer ranges from 100 nm to 10 μm, preferably from 1 μm to 5 μm.

[0268] In the above-mentioned 100nm to 10μm, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 100nm, 200nm, 500nm, 800nm, 900nm, 1μm, 5μm, 10μm, etc., as well as the range values ​​between any two of the above-mentioned point values.

[0269] In the above-mentioned 1μm to 5μm, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 1μm, 2μm, 3μm, 4μm, 5μm, etc., as well as the range values ​​between any two of the above-mentioned point values.

[0270] In one embodiment, the diaphragm is used to be arranged on one side of the positive electrode plate or the negative electrode plate, for example, the diaphragm is arranged between the positive electrode plate and the negative electrode plate, or the diaphragm is arranged on the side of the negative electrode plate away from the positive electrode plate, and the second diaphragm layer is arranged on the side of the first diaphragm layer facing the negative electrode.

[0271] Taking lithium-ion batteries as an example, non-M element cation salts can be non-lithium salts. Considering that these non-lithium salts can electrostatically shield and inhibit the growth of lithium dendrites, which are generally produced at the negative electrode, it is preferred to coat the cation-supplementing material on the side of the diaphragm facing the negative electrode, that is, the second diaphragm layer is arranged on the side of the first diaphragm layer facing the negative electrode.

[0272] In one embodiment, if Figure 6 As shown, the present application also provides a method for preparing a cation-supplementing material, comprising: preparing a prepolymer emulsion of a shell layer; adding a non-M element cation salt solution to the prepolymer emulsion of the shell layer, heating and stirring, to obtain the ion-supplementing material.

[0273] Prepolymer is a substance formed by preliminary polymerization of monomers used to prepare the shell layer.

[0274] Prepolymer emulsion, the state in which the prepolymer is dispersed in water to form an emulsion.

[0275] In order to prepare a cationic supplementing material with a shell layer coated with a non-M element cationic salt, a prepolymer emulsion of the shell layer can be prepared, and a non-M element cationic salt solution is added to the prepolymer emulsion of the shell layer, heated and stirred to obtain an ion supplementing material. That is, the non-M element cationic salt is added to the prepolymer emulsion of the shell layer, and the prepolymer is further polymerized on the surface of the non-M element cationic salt to obtain a shell layer coated with a non-M element cationic salt. It can be understood that the non-M element cationic salt is added to an aqueous solution to obtain a non-M element cationic salt solution.

[0276] In one embodiment, the step of preparing the prepolymer emulsion of the shell layer includes: mixing the monomers constituting the shell layer with a solvent, and heating the mixture to obtain the prepolymer emulsion of the shell layer.

[0277] In one embodiment, the step of mixing the monomers constituting the shell layer with a solvent and heating to obtain a prepolymer emulsion of the shell layer includes: mixing the monomers constituting the shell layer, amino resin monomers, formaldehyde substances, gelatin and water to obtain a mixed solution, adjusting the pH value of the obtained mixed solution to 6.0 to 8.5, heating to 40°C to 70°C, and keeping warm for 20min to 60min to obtain a prepolymer emulsion of the shell layer; wherein the mass of the amino resin monomer is 20% to 70% of the mass of the non-M element cation salt; the formaldehyde substance is 15% to 120% of the mass of the amino resin monomer; and the gelatin is 3% to 16% of the mass of the amino resin monomer.

[0278] For example, taking gelatin-modified amino resin as the shell layer, amino resin monomer, formaldehyde, gelatin and water are mixed, the pH value of the obtained mixed solution is adjusted to 6.0 to 8.5, heated to 40°C to 70°C, and kept warm for 20min to 60min to obtain a gelatin-modified amino resin prepolymer solution; an appropriate amount of non-M element cationic salt is added to the above gelatin-modified amino resin prepolymer solution, the temperature is raised to 40°C to 60°C, and the mixture is stirred thoroughly. The mixture is filtered and vacuum dried at 70°C to obtain a cation-supplementing material.

[0279] It is understood that, in one embodiment, during the preparation of the prepolymer emulsion of the gelatin-modified amino resin, the mass of the amino resin monomer is 20% to 70% of the mass of the non-M element cation salt; the formaldehyde substance is 15% to 120% of the mass of the amino resin monomer; and gelatin is 3% to 16% of the mass of the amino resin monomer. The amino resin monomer is one or more of melamine, urea and phenylguanamine.

[0280] In one embodiment, the step of adding a non-M element cation salt solution to a prepolymer emulsion of a shell layer, heating and stirring to obtain a cation-supplementing material includes: adding a non-M element cation salt solution to a prepolymer emulsion of a shell layer, stirring, heating to 40° C. to 60° C., filtering, and drying to obtain a first layer of shell coating material; wherein the mass ratio of the non-M element cation salt to the prepolymer emulsion of the shell layer is in the range of 1:100 to 1:1.

[0281] The non-M element cation salt solution is added to the prepolymer emulsion of the shell layer, and stirred to fully disperse the non-M element cation salt solution and the prepolymer emulsion of the shell layer, thereby improving the dispersibility of the non-M element cation salt solution, which is helpful for preparing a cation-supplementing material of a suitable size. The prepolymer is polymerized on the surface of the non-M element cation salt solution by heating to 40° C. to 60° C., and a shell layer is formed on the surface of the non-M element cation salt solution to coat the non-M element cation salt solution. The cation-supplementing material is obtained by filtering and drying.

[0282] In one embodiment, after adding a non-M element cationic salt solution to a prepolymer emulsion of a shell layer, stirring, heating to 40° C. to 60° C., filtering, and drying to obtain a first layer shell coating material, the method further includes: mixing the first layer shell coating material with the constituent monomers of the second layer shell and a solvent, adding an initiator, heating, stirring, and drying to obtain a cation-supplementing material; wherein the mass ratio of the first layer shell coating material to the constituent monomers of the second layer shell is in a range of 5% to 50%.

[0283] That is, in order to improve the coating property of the shell layer, a second shell layer is further provided on the surface of the first shell coating material.

[0284] In one embodiment, the step of mixing the first layer shell coating material with the constituent monomers and solvent of the second layer shell, adding an initiator, heating, stirring, and drying to obtain a cation-supplementing material includes: mixing the first layer shell coating material with butadiene, styrene, and THF solvent, adding an initiator, heating, stirring, and drying to obtain a cation-supplementing material; wherein the mass ratio of butadiene to styrene ranges from 1:100 to 100:1.

[0285] That is, in one embodiment, styrene-butadiene rubber polymer can be used as the second shell layer. The styrene-butadiene rubber polymer as the second shell layer improves the density, toughness and heat resistance of the entire shell, thereby improving its thermal processing stability.

[0286] In one embodiment, the present application also provides a battery, comprising the cation-supplementing material as described above; or, comprising the electrolyte as described above; or, comprising the positive electrode plate as described above; or, comprising the negative electrode plate as described above; or, comprising the diaphragm as described above; or comprising the cation-supplementing material obtained by the preparation method of the cation-supplementing material as described above.

[0287] It can be understood that the battery includes battery cells, battery modules, and battery packs.

[0288] In one embodiment, the present application further provides an electrical device, which includes the battery as described above.

[0289] Since the battery adopts all the technical solutions of all the above embodiments, it has at least all the beneficial effects brought by the technical solutions of the above embodiments, which will not be described one by one here.

[0290] In addition, the battery (battery cell, battery module, battery pack) and the electric device of the present application will be described below with reference to the drawings as appropriate.

[0291] In one embodiment of the present application, a battery cell is provided.

[0292] Typically, a battery cell includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the battery charge and discharge process, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through. The separator is the separator improved above in this application.

[0293] The positive electrode plate includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector.

[0294] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0295] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0296] In some embodiments, when the secondary battery is a lithium-ion battery, the positive electrode active material may adopt a positive electrode active material for lithium-ion batteries known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxides (such as LiCoO 2 ), lithium nickel oxide (such as LiNiO 2 ), lithium manganese oxide (such as LiMnO 2 、LiMn 2 O 4 ), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 (Also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O 2 (Also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O 2 (Also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O 2 (Also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O 2 (Also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O 2 ) and its modified compounds, etc. Examples of lithium phosphates containing olivine structures may include, but are not limited to, lithium iron phosphate (such as LiFePO 4 (also referred to as LFP), composite materials of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO 4), at least one of a composite material of lithium manganese phosphate and carbon, a composite material of lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0297] The battery will be accompanied by Li deintercalation and consumption during the charge and discharge process, and the molar content of Li is different when the battery is discharged to different states. In the list of positive electrode materials in this application, the molar content of Li is the initial state of the material, that is, the state before feeding. The positive electrode material is used in the battery system, and the molar content of Li will change after charge and discharge cycles.

[0298] In the list of positive electrode materials in this application, the molar content of O is only a theoretical value. The release of oxygen from the lattice will cause the molar content of oxygen to change, and the actual molar content of O will fluctuate.

[0299] In some embodiments, the positive electrode film layer may also optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0300] In some embodiments, the positive electrode film layer may further include a conductive agent, for example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0301] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0302] The negative electrode plate includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.

[0303] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0304] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0305] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0306] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0307] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0308] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0309] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0310] The electrolyte plays a role in conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs.

[0311] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0312] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0313] In some embodiments, the electrolyte may further include additives that can improve certain properties of the battery, such as additives that improve the overcharge performance of the battery, additives that improve the high or low temperature performance of the battery, etc.

[0314] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous structure separator with good chemical stability and mechanical stability can be selected.

[0315] In some embodiments, the material of the diaphragm can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The diaphragm can be a single-layer film or a multi-layer composite film, without particular limitation. When the diaphragm is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0316] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0317] In some embodiments, the battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.

[0318] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0319] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square or any other shape. Figure 7 The battery cell 5 is a square structure as an example.

[0320] In some embodiments, reference Figure 8, the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the diaphragm can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0321] In some embodiments, battery cells may be assembled into a battery module. The number of battery cells contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.

[0322] Fig. 9 4 is an example of a battery module. Fig. 9 In the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.

[0323] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.

[0324] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.

[0325] Fig.10 and Fig.11 1 is a battery pack 1 as an example. Fig.10 and Fig.11 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0326] In addition, the present application also provides an electrical device, which includes at least one of the battery cells, battery modules, or battery packs provided in the present application. The battery cells, battery modules, or battery packs can be used as power sources for electrical devices, or as energy storage units for electrical devices. Electrical devices may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0327] As an electrical device, a battery cell, a battery module or a battery pack can be selected according to its usage requirements.

[0328] Fig.12 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the power consumption device's requirements for high power and high energy density of battery cells, a battery pack or a battery module can be used.

[0329] As another example, the device may be a mobile phone, a tablet computer, a notebook computer, etc. The device is usually required to be light and thin, and a battery cell may be used as a power source.

[0330] Example

[0331] Example 1

[0332] Preparation of cation-supplementing materials:

[0333] The amino resin monomer (melamine), formaldehyde substances (37% formaldehyde by mass), gelatin and water are mixed in a mass-to-molar ratio of 36:4:3.6:25, the pH value of the obtained mixed solution is adjusted to 7.5, and the mixture is heated to 50°C for 40 minutes to obtain a gelatin-modified amino resin prepolymer emulsion;

[0334] Add a non-lithium ion salt solution (non-M element cation salt solution) (mass concentration of potassium hexafluorophosphate is 30 g / L, and the solvent is water) to the gelatin-modified amino resin prepolymer emulsion, wherein the mass ratio of the non-lithium ion salt solution to the gelatin-modified amino resin prepolymer emulsion is 1:50, heat to 50°C, stir thoroughly, filter, and vacuum dry at 70°C to obtain the first layer of shell coating material.

[0335] 10g of the first shell coating material was added and dispersed into 200ml THF solution containing 1g butadiene and 0.5g styrene (butadiene and styrene are monomers constituting the second shell), 0.1g AIBN was added, and polymerization reaction was carried out at 70 degrees Celsius for 2h, filtered, and vacuum dried at 70°C to obtain a cation-replenishing material, wherein the thickness of the first shell was 40nm, and the thickness of the second shell was 40nm, wherein the shell layer composed of the first shell and the second shell body was fully coated on the surface of the core material composed of non-lithium ion salt. The DV50 of the prepared cation-replenishing material was 200nm.

[0336] (1) Preparation of positive electrode sheet

[0337] Lithium iron phosphate (LiFePO 4 ), Super P as a conductive agent, and polyvinylidene fluoride (PVDF) as a binder are used to make positive electrode slurry in N-methylpyrrolidone (NMP). The solid content in the positive electrode slurry is 50wt%, and the solid content of LiFePO 4 The mass ratio of Super P and PVDF is 95:3:2. The positive electrode slurry is coated on the current collector aluminum foil and dried at 85°C, then cold pressed, trimmed and cut, and dried at 85°C under vacuum for 4 hours to make a positive electrode sheet.

[0338] (2) Preparation of negative electrode sheet

[0339] The first active material of the negative electrode, graphite, the second active material, hard carbon, the conductive agent Super P, the binder styrene butadiene rubber (SBR) and the thickener CMC-Na were dispersed in deionized water at a mass ratio of 90:2:3:1.5:1.5 and mixed evenly to obtain a negative electrode slurry. The negative electrode slurry was coated on the negative electrode current collector copper foil and dried at 85°C, then cold pressed, trimmed, cut into pieces, and dried at 120°C under vacuum conditions for 12 hours to make a negative electrode sheet.

[0340] (3) Isolation film

[0341] A 16 μm polyethylene film was selected as the isolation film.

[0342] (4) Preparation of electrolyte

[0343] The electrolyte is 1M lithium hexafluorophosphate + 1wt% potassium hexafluorophosphate cation-replenishing material, and the mass of the cation-replenishing material accounts for 1% of the mass of the electrolyte.

[0344] (5) Preparation of batteries

[0345] The positive electrode sheet, separator, and negative electrode sheet prepared in the above steps are stacked in order, so that the separator is placed between the positive and negative electrode sheets to play the role of isolating the positive and negative electrodes, and the bare battery cell is wound, and the pole ears are welded, and the bare battery cell is placed in an outer package. The electrolyte prepared above is injected into the dried battery cell, and after packaging and standing, it is slowly formed, and then shaped to prepare a lithium-ion battery.

[0346] Example 2

[0347] On the basis of Example 1, the non-M element cation salt is replaced with sodium hexafluorophosphate to obtain Example 2.

[0348] Example 3 to Example 6

[0349] On the basis of Example 1, the mass percentage of the cation-supplementing material in the electrolyte was adjusted to obtain Example 3 and Example 6.

[0350] Example 7 and Example 8

[0351] On the basis of Example 1, the mass percentage of the non-M element cation salt in the entire cation-supplementing material was adjusted to obtain Example 7 and Example 8.

[0352] Example 9 to Example 11

[0353] On the basis of Example 1, the cation-supplementing material is added to the negative electrode plate, and the cation-supplementing material is directly added during the preparation process of the negative electrode plate to obtain Examples 9 to 11.

[0354] Example 12 to Example 14

[0355] On the basis of Example 1, the cation-supplementing material is added to the diaphragm. The cation-supplementing material is directly added during the preparation process of the diaphragm to obtain Examples 12 to 14.

[0356] Example 15 to Example 17

[0357] On the basis of Example 1, the cation-supplementing material is added to the positive electrode plate, and the cation-supplementing material is directly added during the preparation process of the positive electrode plate to obtain Examples 14 to 17.

[0358] Example 18 and Example 19

[0359] On the basis of Example 1, the Dv50 of the cation-supplementing material and the thickness of the first shell layer and the second shell layer were adjusted to obtain Example 18 and Example 19.

[0360] Comparative Example 1

[0361] On the basis of Example 1, 0.8% by mass of potassium hexafluorophosphate was directly added to the electrolyte.

[0362] Comparative Example 2

[0363] On the basis of Example 1, no cation-supplementing material is added to the electrolyte, so that no cation-supplementing material is added to the entire battery.

[0364] Performance Testing

[0365] Electrochemical performance test: The above lithium-ion battery was cycled using a 0.5C / 0.5C constant current charge and discharge method at a temperature of 45°C and a voltage range of 2.5-3.65V. During the cycle, the battery was high-voltage cation supplemented every 50 cycles, specifically by charging to 4.3V at a 0.1C constant current, and then tested according to normal cycle charge and discharge.

[0366] To maintain consistency, the comparative examples were also tested in the same manner as above.

[0367] Table 1 List of Examples

[0368]

[0369] Table 2 Example List

[0370]

[0371] It can be seen from the test results in Table 1 that compared with the comparative example, the embodiment adds a cation-supplementing material, and the cation-supplementing material includes a core material (including a non-M element cation salt) and a shell layer that completely covers the surface of the core material. It can be seen that after the battery in the embodiment is cycled 400 times, its capacity retention performance is improved, indicating that the cation-supplementing material of the present application can improve the cycle performance of the battery.

[0372] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the contents of the present invention's specification and drawings, or directly / indirectly applied in other related technical fields, are included in the patent protection scope of the present invention.

Claims

1. A cation-supplementing material, applied to M-element batteries, characterized in that: It comprises a shell layer and a core material arranged in the shell layer, wherein the core material comprises a non-M element cation salt.

2. The cation-supplementing material according to claim 1, characterized in that The non-M element cation in the non-M element cation salt includes at least one of a Group IA element cation or a Group IIA element cation.

3. The cation-supplementing material according to claim 1 or 2, characterized in that: The M element battery comprises a lithium battery, and the non-M element cation in the non-M element cation salt comprises one or more of potassium ion, sodium ion, barium ion, cesium ion, rubidium ion and calcium ion; Alternatively, the M element battery comprises a sodium battery, and the non-M element cations in the non-M element cation salt comprise one or more of potassium ions, lithium ions, barium ions, cesium ions, rubidium ions and calcium ions.

4. The cation-supplementing material according to any one of claims 1 to 3, characterized in that The anions in the non-M element cation salt include at least one of perchlorate, tetrafluoroborate, hexafluoroarsenate, hexafluorophosphate, bistrifluoromethylsulfonyl imide, difluorophosphate, bisdifluorosulfonyl imide, bisoxalate borate and difluorooxalate borate, nitrate, sulfate, sulfite, and trifluoromethanesulfonyl.

5. The cation-supplementing material according to any one of claims 1 to 4, characterized in that The mass percentage of the non-M element cation salt to the mass of the cation-supplementing material is 50% to 99%, preferably 70% to 95%.

6. The cation-supplementing material according to any one of claims 1 to 5, characterized in that The Dv50 value of the cation-supplementing material is in the range of 100 nm to 10 μm, preferably, 200 nm to 2 μm.

7. The cation-supplementing material according to any one of claims 1 to 6, characterized in that The thickness of the shell layer ranges from 20 nm to 800 nm, preferably from 50 nm to 200 nm; And / or, the shell layer completely covers the surface of the core material.

8. The cation-supplementing material according to any one of claims 1 to 7, characterized in that The material of the shell layer includes at least one of a gelatin-modified amino resin composite material, a styrene-butadiene rubber polymer, and an acrylate polymer.

9. The cation-supplementing material according to any one of claims 1 to 8, characterized in that The shell layer includes at least two shell layers, at least one shell layer is arranged on the surface of the core material, and at least another shell layer is arranged on a side of the at least one shell layer away from the core material; And / or, the shell layer comprises at least two shell layers, at least one shell layer is arranged on the surface of the core material, and at least another shell layer is arranged on a side of the at least one shell layer away from the core material, and the thickness of the at least one shell layer ranges from 10nm to 400nm, preferably, from 30nm to 150nm; And / or, the shell layer includes at least two shell layers, at least one shell layer is arranged on the surface of the core material, and at least another shell layer is arranged on the side of the at least one shell layer away from the core material, and the thickness range of the at least another shell layer is 10nm to 400nm, preferably, 30nm to 150nm.

10. The cation-supplementing material according to claim 9, characterized in that: The material of the at least one shell layer includes a gelatin-modified amino resin composite material; And / or, the material of the at least another shell layer includes at least one of styrene-butadiene rubber polymer and acrylate polymer.

11. An electrolyte, characterized in that: The electrolyte comprises the cation-supplementing material according to any one of claims 1 to 10.

12. The electrolyte according to claim 11, characterized in that The mass percentage of the cation-supplementing material to the total mass of the electrolyte is 1% to 100%, preferably 5% to 20%.

13. The electrolyte according to claim 11 or 12, characterized in that The mass percentage of the non-M element cation salt in the cation-supplementing material to the total mass of the electrolyte is 0.0001% to 50%, preferably 0.5% to 10%.

14. The electrolyte according to any one of claims 11 to 13, characterized in that The electrolyte includes a lithium salt, and the lithium salt includes at least one of lithium perchlorate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium difluorophosphate, lithium bis(difluorosulfonyl)imide, lithium bis(oxalatoborate), lithium difluorooxalatoborate, and lithium trifluoromethanesulfonyl; And / or, the electrolyte includes a solvent, and the solvent includes at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and fluoroethylene carbonate.

15. A positive electrode sheet, characterized in that: The positive electrode plate comprises the cation-supplementing material according to any one of claims 1 to 10.

16. The positive electrode sheet according to claim 15, characterized in that: The positive electrode plate includes a positive electrode current collector and a positive electrode coating disposed on the positive electrode current collector, and the mass percentage of the cation-supplementing material to the total mass of the positive electrode coating is 0.5% to 20%, preferably 1% to 5%.

17. The positive electrode sheet according to claim 16, characterized in that: The positive electrode coating includes a binder, and the mass percentage of the binder in the positive electrode coating to the total mass of the positive electrode coating is 0.5% to 10%, preferably 1% to 3%.

18. The positive electrode sheet according to any one of claims 15 to 17, characterized in that: The positive electrode sheet comprises a positive electrode current collector and at least two positive electrode coatings disposed on the positive electrode current collector, at least one positive electrode coating is disposed on the positive electrode current collector, and at least another positive electrode coating is disposed on a side of at least one positive electrode coating away from the positive electrode current collector; Define that the mass percentage of the cation-replenishing material in at least one of the positive electrode coatings is W1, and the mass percentage of the cation-replenishing material in at least another of the positive electrode coatings is W2, and W2 is greater than W1.

19. A negative electrode plate, characterized in that: The negative electrode plate comprises the cation-supplementing material according to any one of claims 1 to 10.

20. The negative electrode sheet according to claim 19, characterized in that: The negative electrode plate comprises a negative electrode current collector and a negative electrode coating disposed on the negative electrode current collector, and the mass percentage of the cation-supplementing material to the total mass of the negative electrode coating is 0.5% to 40%, preferably 1% to 5%.

21. The negative electrode sheet according to claim 20, characterized in that: The negative electrode coating includes a binder, and the mass percentage of the binder in the negative electrode coating to the total mass of the negative electrode coating is 0.5% to 15%, preferably 1% to 5%.

22. The negative electrode sheet according to any one of claims 18 to 20, characterized in that: The negative electrode sheet comprises a negative electrode current collector and at least two negative electrode coatings disposed on the negative electrode current collector, at least one of the negative electrode coatings is disposed on the negative electrode current collector, and at least another of the negative electrode coatings is disposed on a side of at least one of the negative electrode coatings away from the negative electrode current collector; It is defined that the mass percentage of the cation-replenishing material in at least one of the negative electrode coatings is W3, and the mass percentage of the cation-replenishing material in at least another of the negative electrode coatings is W4, and W4 is greater than W3.

23. A diaphragm, characterized in that: The separator comprises the cation-supplementing material according to any one of claims 1 to 10.

24. The diaphragm according to claim 23, characterized in that The mass percentage of the cation-supplementing material to the mass of the separator is 10% to 200%, preferably 50% to 100%.

25. The diaphragm according to claim 23 or 24, characterized in that The separator includes a first separator layer and a second separator layer disposed on the first separator layer, and the second separator layer includes the cation-supplementing material.

26. The diaphragm according to claim 25, characterized in that The thickness of the second diaphragm layer is in the range of 100 nm to 10 μm, preferably, 1 μm to 5 μm; And / or, the diaphragm is arranged on one side of the positive electrode sheet or the negative electrode sheet, and the second diaphragm layer is arranged on the side of the first diaphragm layer facing the negative electrode sheet.

27. A method for preparing a cation-supplementing material according to any one of claims 1 to 10, characterized in that: include: preparing a prepolymer emulsion for a shell layer; The non-M element cation salt solution is added into the prepolymer emulsion of the shell layer, heated and stirred to obtain the cation supplement material.

28. The method for preparing a cation-supplementing material according to claim 27, characterized in that: The step of preparing the prepolymer emulsion of the shell layer includes: mixing the constituent monomers of the shell layer with a solvent, and heating the mixture to obtain the prepolymer emulsion of the shell layer.

29. The method for preparing a cation-supplementing material according to claim 28, wherein: The step of mixing the monomers constituting the shell layer with the solvent and heating to obtain the prepolymer emulsion of the shell layer comprises: Mixing the monomers constituting the shell layer, amino resin monomers, formaldehyde substances, gelatin and water to obtain a mixed solution, adjusting the pH value of the obtained mixed solution to 6.0 to 8.5, heating the mixed solution to 40° C. to 70° C., and keeping the temperature for 20 to 60 minutes to obtain a prepolymer emulsion of the shell layer; The mass of the amino resin monomer is 20% to 70% of the mass of the non-M element cationic salt; the formaldehyde substance is 15% to 120% of the mass of the amino resin monomer; and the gelatin is 3% to 16% of the mass of the amino resin monomer.

30. The method for preparing a cation-supplementing material according to any one of claims 27 to 29, characterized in that: The step of adding a non-M element cation salt solution to the prepolymer emulsion of the shell layer, heating and stirring to obtain a cation-supplementing material comprises: Adding a non-M element cation salt solution to the prepolymer emulsion of the shell layer, stirring, heating to 40° C. to 60° C., filtering, and drying to obtain a first layer of shell coating material; The mass ratio of the non-M element cation salt to the prepolymer emulsion of the shell layer is in the range of 1:100 to 1:

1.

31. The method for preparing a cation-supplementing material according to claim 30, wherein: After the steps of adding the non-M element cation salt solution to the prepolymer emulsion of the shell layer, stirring, heating to 40° C. to 60° C., filtering, and drying to obtain the first layer of shell coating material, the method further comprises: The first layer shell coating material is mixed with the constituent monomers of the second layer shell and a solvent, an initiator is added, and the mixture is heated, stirred, and dried to obtain a cation-supplementing material; The mass ratio of the first shell coating material to the second shell constituent monomers is in the range of 5% to 50%.

32. The method for preparing a cation-supplementing material according to claim 31, wherein: The step of mixing the first layer shell coating material with the constituent monomers of the second layer shell and a solvent, adding an initiator, heating, stirring and drying to obtain a cation-supplementing material comprises: The first layer of shell coating material is mixed with butadiene, styrene and THF solvent, an initiator is added, and the mixture is heated, stirred and dried to obtain a cation-supplementing material; Wherein, the mass ratio of the butadiene to the styrene ranges from 1:100 to 100:

1.

33. A battery, characterized in that: The battery comprises a cation-supplementing material as claimed in any one of claims 1 to 10; Or, comprising the electrolyte as claimed in any one of claims 11 to 14; Or, comprising a positive electrode sheet as claimed in any one of claims 15 to 18; Or, comprising a negative electrode sheet as claimed in any one of claims 19 to 22; Or, comprising a diaphragm as claimed in any one of claims 13 to 26; Alternatively, the cation-supplementing material comprises a cation-supplementing material obtained by the method for preparing the cation-supplementing material according to any one of claims 27 to 32.

34. An electrical device, characterized in that: The electrical device comprises the battery as claimed in claim 33.